The Use of Storytelling to Improve EFL Learners' Vocabulary Case study: Second year learners of Baali Mohammed Middle School ,M'sif- M'sila - LEBOUKH Souaad (UNIVERSITÉ MOHAMED BOUDIAF - M’SILA, 2024)
This study investigates the effectiveness of using the Storytelling (ST) technique in enhancing learners’ vocabulary acquisition. To achieve this objective, a quasi-experimental design was employed, where learners were exposed to storytelling as a teaching strategy. The research utilized two vocabulary tests: a pre-test, administered to evaluate students’ initial vocabulary level, and a post-test, aimed at measuring vocabulary improvement following the intervention. The study sample comprised of 32 second-year middle school learners . In addition to the pre- and post-tests, an observation checklist was utilized to assess learners' motivation and engagement during the storytelling sessions. This checklist was designed to monitor learners' active participation, concentration, and interest throughout the intervention. The collected data from the observation checklist provided valuable insights into students' levels of motivation, engagement, participation, vocabulary use, and short-term retention, which were crucial for evaluating the overall effectiveness of the storytelling technique. The findings strongly indicate that storytelling is a powerful pedagogical strategy for enhancing vocabulary learning among EFL learners in middle school. These results affirm that the use of storytelling as an instructional tool has a significant positive impact on vocabulary acquisition and retention
Keywords: Storytelling; Vocabulary; EFL; Middle School Pupils.